Becoming Adult, Becoming Christian Adult Development and Christian Faith - Fowler, James W (San Francisco Harper & Row, 1984)
Fowler presents in Becoming Adult, Becoming Christian the four dominant adult development theories today, highlighting their images of wholeness, maturity, and human potential. His discussion probes Erikson's existential psychology; Daniel Levinson's Se
Keywords: Faith -- Psychology. Faith development. Adulthood -- Psychological aspects